Optimal sizing procedure for hybrid solar wind power systems by fuzzy logic - La Terra, G.; Salvina, G.; Tina, G. M. (MELECON 2006 - 2006 IEEE Mediterranean Electrotechnical Conference, 2006)
This paper refers about an automatic procedure to perform the optimal sizing of a grid connected hybrid solar wind power system (HSWPS) developed by a fuzzy logic based multi-objective optimization approach. Both technical and economical objective functions are taken into account in the optimisation procedure; the technical objective, related to system reliability, is expressed by the energy index of reliability. For this purpose a probabilistic model for HSWPS has been developed, based on the convolution technique to assess the long term performance for both stand-alone and grid-linked applications. The proposed model is based on closed form solution approach to treat the wind system and the solar system as a whole. The procedure of optimization aims at finding the configuration that yields the best compromise for the two considered objectives: the long-term average performance and the overall cost of the generating system.